(untitled) (Marketing Journal, 2025)
The study analyzes the essence of the Triple Helix model, the open innovation model, the cluster development model, the business incubation model, the public - private partnership model, and other innovative approaches widely used in attracting foreign inves tment, and their impact on the economy. The author examines current trends in attracting foreign investment, problems that hinder their increase, and solutions based on the proposed models. 573